Composition and microstructure of concrete mixtures subjected to biogenic acid corrosion and their role in corrosion prediction of concrete outfall sewers - Kiliswa, Moses Wopicho (Concrete Materials and Structural Integrity Research Unit (CoMSIRU), 2016)
Wastewater conveyance and treatment facilities, which include outfall sewers, manholes, and treatment works, are among the key constituents of a country's infrastructure. Most of these facilities are made of concrete due to its low production costs, versatility, inherent strength and durability under most conditions. However, under certain conditions, sewage that is conveyed through outfall sewers becomes septic and hydrogen sulphide (H2S) gas is generated. When this gas is released from the sewage and absorbed onto the moist concrete sewer pipe walls, it is microbially converted by sulphide-oxidising bacteria to sulphuric acid (biogenic H2SO4) which reacts with the acid-soluble components of concrete causing it to corrode. In principle, the biogenic H2SO4 concrete corrosion mechanism entails simultaneous destruction of the calcium hydroxide (CH) in the hydrated cement paste (HCP) and substituting a larger molecule of calcium sulphate into the concrete matrix thus causing pressure and spalling of the adjacent concrete and aggregate particles. In addition, the calcium sulphate precipitates as gypsum which reacts with various aluminates to form secondary ettringite. These mechanisms lead to the loss of stiffness and strength, accompanied by expansion and cracking, and eventually transformation of the affected concrete matrix into a soft and pulpy non-cohesive layer. The biogenic concrete corrosion rate depends, inter alia, on the chemical composition of binders (cement and supplementary cementitious materials (SCMs)) and microstructural characteristics of concrete mixtures used in the manufacture of sewer pipes. The needed properties of concrete mixtures for sewer pipe applications can be determined by biogenic corrosion prediction models, such as the widely used deterministic (mechanistic) Life Factor Method (LFM). The service life of wastewater treatment facilities made of concrete depends on the input parameters in corrosion prediction models. The motivation behind the current study was based on the need to improve the ability to predict the design life of concrete sewers by improving the input parameters in the LFM, which is used in South Africa. The design life of concrete sewers in South Africa has traditionally been 40 years. The main objective of the current study was to characterise the microstructure of both Portland cement (PC) and calcium aluminate cement (CAC) based concrete mixtures that had been subjected to biogenic corrosion mechanisms in an operational sewer environment for approximately 127 months (10½ years); further, based on the understanding of the underlying mechanisms of attack, proposals were made to improve the LFM, for which the corrosion rate-controlling input parameter, referred to as alkalinity (or equivalent CaCO3, as a summation for both binder and aggregate) is based on the characteristics of plain PC-based binder systems. In addition to the main objective above, a parallel study was undertaken to characterise parameters that influence biogenic concrete corrosion rates based on measurements taken in two sewer environments/sites in different geographical locations in South Africa. One of the study sites was the Virginia Experimental Sewer (VES) in Virginia, Free State Province, while the other site was a manhole within the Langa Pump Station in Cape Town, Western Cape Province. The VES consists of 900 mm diameter by 300 mm long concrete pipe samples made from both PC- and CAC-based (plain and blended) binder systems, the top 120° being cut to form 'lids', so that they are removable. The removable 'lids' enable scheduled observations and sample recovery to be undertaken. Moreover, the 'lids' also act as windows through which core samples can be placed in plastic baskets that are hung at certain sections in the sewer headspace, so that they can be accessed for monitoring.